ANALISIS ANALISIS KINERJA KEUANGAN KOPERASI STUDI PADA KOPERASI NUSANTARA: ANALISIS KINERJA KEUANGAN KOPERASI STUDI PADA KOPERASI NUSANTARA - aditiya, nanda yoga (Medikonis, 2025)
Study This aim For evaluate performance finance based on ratio liquidity , ratio solvency , ratio profitability in Cooperatives archipelago from 2022-2023 . Data used in study This is secondary data form report finance officially obtained​ from Archipelago Cooperative . Analysis used​ is analysis descriptive quantitative . Guided by the Regulations Deputy Field Supervision Ministry Cooperatives and SMEs Number 06/Per/Dep. 6./ IV/2016 concerning guidelines evaluation performance cooperative . Based on research, analysis of liquidity, solvency and profitability performance in highlighting important aspects of the cooperative's financial sustainability. Research results showing ratio liquidity deep average four know final with mark percentage 15.12% then can categorized as Good . Average value of the ratio solvency in four year cooperative archipelago from in 2020-2023 amounting to 74.94% with category good , average value​ ratio profitability amounting to 10.81% with category said Enough Good . This analysis provides a comprehensive picture of the cooperative's financial health, highlighting the importance of financial ratios in evaluating the cooperative's financial performance.